Critical Review on Carbon Dioxide Sequestration Potentiality in Methane Hydrate Reservoirs via CO2–CH4 Exchange: Experiments, Simulations, and Pilot Test Applications - Mwakipunda, Grant Charles; Abelly, Elieneza Nicodemus; Mgimba, Melckzedeck Michael; Ngata, Mbega Ramadhani; Nyakilla, Edwin E.; Yu, Long (Energy & fuels, 2023)
Many researchers have investigated the potential of methane hydrate reservoirs (MHRs) for carbon dioxide (CO2) sequestration and methane (CH4) production through the CO2–CH4 replacement method. This technique is not yet commercially implemented due to various limitations, especially economic reasons. This study investigated recent advancements in MHRs potentiality for CO2 sequestration through CO2 or mixed gas exchange injection while recovering CH4. From the experiments, modeling, and simulations, and one pilot test conducted, it was found that there is a great potentiality of sequestrating CO2 in MHRs while recovering CH4. In addition, it was revealed that to produce more CH4, the nitrogen/hydrogen (N2/H2) mole fraction in the injector gas stream should be more significant than that in CO2, while to sequestrate more CO2, the CO2 mole fraction in the injector gas stream should be greater than the N2/H2 mole fraction. The CO2–mixture gases mole fraction ratio recommended from one successful pilot test conducted was 23:77 (CO2/N2), which revealed that approximately 60% of injected CO2 was sequestrated with 855 × 103 standard cubic feet of CH4 produced. The challenges identified in this review will urge researchers to explore suitable technologies to conduct more pilot tests and pave the way toward entire field operations on CO2 sequestration in MHRs toward decarbonization.